Pengaruh Self Esteem Dan Self Efficacy Terhadap Kinerja Pegawai Melalui Komitmen Kerja Sebagai Variabel Intervening Pada Dinas Perhubungan Kota Padang - Nava Kurnia Mulia; Yulasmi Yulasmi (Management Studies and Business journal, 2025)
This study aims to identify and attempt to analyze the effect of self-esteem and self-efficacy on employee performance through work commitment as an intervening variable at the Padang City Transportation Agency. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this study are employees of the Padang city transportation service. The results of the study found that there is a positive and significant influence between Self Esteem on Work Commitment. There is a positive and insignificant effect between Self Efficacy on Work Commitment. There is a positive and insignificant effect between Self Esteem on Employee Performance. There is a negative and insignificant effect between Self Efficacy on Employee Performance. There is a positive and significant influence between Work Commitment on Employee Performance. Work Commitment mediates Self Esteem on Employee Performance. Work Commitment does not mediate Self Efficacy on Employee Performance